2015
DOI: 10.3399/bjgp15x686965
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, severity, help seeking, and management of uncomplicated urinary tract infection: a population-based survey

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
121
4
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(144 citation statements)
references
References 22 publications
8
121
4
11
Order By: Relevance
“…Fast 40 % der Frauen erkranken mindestens einmal im Leben an einer symptomatischen Harnwegsinfektion. Die Prävalenz nimmt mit dem Alter zu [2,3,10].…”
Section: Hintergrundunclassified
“…Fast 40 % der Frauen erkranken mindestens einmal im Leben an einer symptomatischen Harnwegsinfektion. Die Prävalenz nimmt mit dem Alter zu [2,3,10].…”
Section: Hintergrundunclassified
“…Uncomplicated urinary tract infections (UTIs) are common in women and are usually managed in primary care [1,2]. Primary care physicians mainly prescribe antibiotics [3,4], as recommended by most guidelines [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic treatment with nonsteroidal anti-in ammatory drugs (NSAIDs) is also recommended by several guidelines for women with mild to moderate symptoms [6][7][8]. However, many women seem to prefer not to take antibiotics and to handle UTI symptoms with NSAIDs and other measures or remedies, presumably from their knowledge of potential harms of antibiotics and especially when they were encouraged by their physicians to delay antibiotic treatment [1,9,10]. In Germany, women who forego antibiotics do not have directs costs, since consultations and most of the drugs costs are covered by the health insurance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Acute cystitis affects several facets of a patient's life: social and intimate relationships, self-esteem, and the ability to work. Depending on the situation, the impact can vary from being slight to very signi cant [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Physicians overestimate patients' desire to take an antibiotic [16]. Patients do not always take the prescribed treatment [4]. Several authors have suggested a shared decision-making approach in uUTI [18] [19].…”
Section: Introductionmentioning
confidence: 99%